Voltage differencing buffered amplifier based low power, high frequency and universal filters using 32 nm CNTFET technology. (January 2021) - Mamatov, Islombek; Özçelep, Yasin; Kaçar, Fırat
Abstract: This work presents filter applications of carbon nanotube field effect transistors (CNTFET) voltage differencing buffered amplifier (VDBA) based high frequency universal filters using 32 nm CNTFET technology of Stanford University model. CNTFETs are potential candidates to replace conventional silicon-based transistors due to their exceptional material properties. In addition, by changing chirality of carbon nanotube (CNT), the material property can be easily changed from semiconducting material to metallic. The VDBA is an active element of circuit which has high input impedance and low output impedance. These types of blocks provide an advantage for voltage mode circuits allowing cascadability and no critical component matching. The proposed CNTFET VDBA shows much higher frequency response with about 67 GHz at first stage which is well known OTA block and around 30 GHz at second stage, power consumption around 135 times less than 0.35 μm TSMC technology and 2476 times reduction in active area of chip. HSPICE and MATLAB simulation tools are used to perform all simulations.